Improving some growth characteristics, quantitative and qualitative characteristics of carcass meat of male Awassi lambs by using palm oil - Kuttar, Ahmed Hussein; Abdullah, Mahfoodh Khaleel (Journal of agricultural, environmental and veterinary sciences, 2023)
The purpose of the study was to examine the effects of adding palm oil (PO) to the treatments on the growth and quantitative characteristics of the meat of male Awassi lambs. As (12) Awassi males were used locally, their ages ranged between 4-4.5 months, with an average live weight of 22.16 ± 0.85 kg. Throughout the characteristics, the animal weights were noted weekly (120 days). Up to the conclusion of the study period, all lambs were killed, skinned, and hollowed out. These were the outcomes: The amount of total intake of concentrated feed was substantially higher (P < 0.01) in the treatments containing 4 and 6% (PO) and T1 than in the treatment containing 2%. (PO). In the same context, the treatment containing 6% (PO) and T1 also outperformed the treatment containing 2% (PO) highly significantly (P < 0.01) in the daily intake of concentrated feed, While the (PO) treatments recorded a highly significant decrease (P < 0.01) in the total intake of hay feed when compared to (T1), In the same context, the (PO) treatments recorded a highly significant decrease (P < 0.01) in the total and daily intake of concentrated and (T1). When compared to T1, the end weight, daily weight gain, and overall weight gain all showed extremely significant superiority (P < 0.01) for the fourth treatment. All study criteria have seen an improvement in feed conversion efficiency. • When compared to T1, the treatments (PO) (the third and fourth) significantly outperformed (P < 0.01) T1 In terms of average final weight, empty body weight, and the percentage of dressings based on hot and cold carcass weight. In the same vein, the fourth treatment significantly outperformed (P < 0.01) T1 and the other (PO) treatments in terms of carcass weight based on hot and cold weight. • The treatment containing 6% (PO) had a highly significant superiority (P < 0.01) in the thickness of the fat layer compared to the other study treatments, and the treatment containing 6% (PO) had a highly significant superiority (P < 0.01) in the characteristic of ocular muscle area, including control, compared to the treatment containing 4% (PO).